Catalytic effect of Fe@Fe2O3 nanowires and Fenton process on carbamazepine removal from aqueous solutions using response surface methodology - M.M. Amin; S. Yousefinejad; M. Dehghani; S. Rahimi (Global Journal of Environmental Science and Management)
Carbamazepine is one of the hydrophilic compounds identified in aquatic environments. Due to toxicity and bio-stability of this psychotropic pharmaceutical in the environment and humans, its removal efficiency and mineralization are important. In this study, synthesized Fe@Fe2O3 nanowires were applied to improve Fenton oxidation process using FeCl3.6H2O and NaBH4. The effects of different parameters such as initial pH, H2O2, FeSO4.7H2O, carbamazepine concentrations, oxidation time, and nanowires dose were evaluated using response surface methodology. After scanning electron microscopy, energy-dispersive X-ray spectroscopy and X-ray diffract meter analysis, Fe@Fe2O3 morphology was synthesized in the form of nanowires with diameters of about 40-80 nm. The optimum oxidation conditions for carbamazepine were established at pH= 4.3, reaction time of 45.9 min, nanowire dose of 179.4 mg/L as well as H2O2, FeSO4.7H2O and carbamazepine concentrations of 22, 52.2 and 7.7 mg/L, respectively. The oxidation efficiency (99.5%) achieved under the optimum condition, which was determined by the model, was consistent with the efficiency predicted by the model. The multi-parameter models showed good calibration and prediction abilities with R2= 0.922, R2adj= 0.907, R2pred= 0.868. According to the results, the carbamazepine degradation rate increased with the increase of Fe2+ due to the synergistic effect between Fe@Fe2O3 and Fe2+ on the catalytic decomposition of H2O2 and generation of OH•. It was concluded that the Fenton process based on the Fe@Fe2O3 nanowires can increase the carbamazepine oxidation rate in aqueous solutions. This method can also be used as an effective and pre-treatment process in the conventional treatment plants.